2020
DOI: 10.1088/1755-1315/560/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Study on Bearing Capacity Influence Factors of the PBL Shear Connector

Abstract: In order to study the main influencing factors of the ultimate bearing capacity of the PBL connector, the large-scale nonlinear finite element analysis software ABAQUS was used to establish the solid model of the PBL connector, and the accuracy of the model was verified by comparison with the test results. Based on this, the main influencing factors of the ultimate bearing capacity of PBL connectors are analyzed. The results show that it is feasible to apply ABAQUS to the finite element analysis of the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Experiment models all complied with the Code for Composite Shi et al (2020) and referred to the Code for Design of Highway Steel-Concrete Composite Girder Bridges (JTG/T D64-01-2015) in China. The push-out experiment, containing 14 specimens, designed seven groups specimens of PBL shear connectors with different corrosion times, numbered SP-0-1, SP-0-2, SP-1-1, SP-1-2, SP-4-1, SP-4-2, SP-12-1, SP-12-2, SP-24-1, SP-24-2, SP-48-1, SP-48-2, SP-72-1, SP-72-2.…”
Section: Experimental Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment models all complied with the Code for Composite Shi et al (2020) and referred to the Code for Design of Highway Steel-Concrete Composite Girder Bridges (JTG/T D64-01-2015) in China. The push-out experiment, containing 14 specimens, designed seven groups specimens of PBL shear connectors with different corrosion times, numbered SP-0-1, SP-0-2, SP-1-1, SP-1-2, SP-4-1, SP-4-2, SP-12-1, SP-12-2, SP-24-1, SP-24-2, SP-48-1, SP-48-2, SP-72-1, SP-72-2.…”
Section: Experimental Programmentioning
confidence: 99%
“…Therefore, for PBL shear connectors, Yu demonstrated that concrete grade and penetrated steel bars played a significant role in the elastic bearing capacity and ultimate bearing capacity, respectively (Yu et al, 2012). In the approaches of Shi et al (2020), and Oguejiofor and Hosain (1994), they assessed that the concrete strength, reinforcement diameter, and the number of holes marked affected the stress of PBL connectors, but hole diameter had little effect. Furthermore, the spacing and diameter of reinforcement affected the load and slip distribution, as did concrete strength.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al analyzed the influence of various factors on the shear capacity of PBL connectors through push-out tests and, on this basis, proposed a formula for calculating the shear capacity of PBL connectors [ 20 , 21 ]. Through numerical simulation and parameter analysis, Shi et al found that the strength of concrete, the diameter of the steel bar and the number of openings significantly affect the force of PBL connectors; however, the diameter of the openings has little effect on it [ 22 ]. Akinori et al studied the influence of the connector’s internal components on the shear performance of the connector through push-out tests and numerical simulation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shear keys have made a great contribution to the development of steel-concrete composite structures by transferring shear forces from the longitudinal direction in the structure, resisting the slippage of concrete and steel plates, and lifting steel plates [1]. With the development of the bridge, shear connection keys have also been developed accordingly, and the more widely used shear keys in engineering can be divided into rigid shear keys and flexible shear keys.…”
Section: Introductionmentioning
confidence: 99%